Shaping Customer Loyalty of Organic Food Products - Mariola MICHAŁOWSKA (Communications of International Proceedings, 2024)
The growing interest of consumers in organic products necessitates a different perspective on customer loyalty, particularly regarding the factors that determine it. The aim of this article is to identify the factors influencing consumer behavior in terms of their loyalty to organic products. The research procedure utilized literature on the subject to gather information on existing studies, data from Eurostat, FIBL, and IFOAM databases, as well as data collected by IJHARS, showing the state of development of the organic market from 2004 to 2022. Additionally, it presents the results of research conducted among consumers of organic food products from the Lubuskie Voivodeship. The selection of respondents was random, using the stratified sampling method according to age range. The conducted research shows that customer loyalty results from positive experiences with organic food products and points of sale, which correlates with high trust. These customers are inclined to recommend both the products and the points of sale of organic food. The presented research fills a gap in the existing literature. Firstly, it identifies and assesses the factors influencing the level of loyalty in the purchasing decisions of consumers in the organic products market. Secondly, it indicates the desired directions for actions taken by producers and suppliers of food products to skillfully shape relationships with customers based on trust and loyalty, allowing for better adjustment of the offer to the needs and expectations of consumers in the organic food market.
Keywords: consumer loyalty; determinants; organic products; Lubuskie Voivodeship.